Implementing Programme Related to Gender Inclusion on Local Government in Nepal - Sijapati, D.B. (Journal of Population and Development, 2021)
This article focuses on practice of the gender inclusion in local government based in Lalitpur and Jhapa districts of some local level. It is find out practices of gender inclusion police of local level and to explore the practices on the different development paradigm. This article used indifferent type’s of methods and data collection procedure. Basically, information needs to answer the research queries are collected from primary and secondary sources of information. The construction questionnaire for information is collected through the literature review and several qualitative and quantitative approaches. At last SPSS (Statistical Package for the Social Science is used to compute the data. Among the total respondents, 35.3 percent are participation for plans formulation related to income generation progarammes, 31.4 percent plans are related to empowerment and leadership programmes, 21 percent plans are related to gender awareness and violence and only 2 percent plans are related to save cyber-crime. More than 6 percent respondents said that only ward representatives are involved in planning of program activities, 31.4 percent respondents said that only municipality authorities and ward representatives are involved and 59.3 percent respondents said that the local government representatives and all social activist are involved in planning of different program activities. Empirical evidence shows that gender inequality, including from legal gender-related restrictions, leads to the loss of growth opportunities, particularly in countries at earlier stages of development. The adverse effect of legal barriers to women’s participation in economic activities remains significant for countries at different stages of development.